Answer:
k =1
Explanation:
Solve for k:
0.5 k + 2.5 = 2 (k + 0.5)
Expand out terms of the right hand side:
0.5 k + 2.5 = 2 k + 1
Subtract 2 k from both sides:
(0.5 k - 2 k) + 2.5 = (2 k - 2 k) + 1
0.5 k - 2 k = -1.5 k:
-1.5 k + 2.5 = (2 k - 2 k) + 1
2 k - 2 k = 0:
2.5 - 1.5 k = 1
Subtract 2.5` from both sides:
(2.5 - 2.5) - 1.5 k = 1 - 2.5
2.5 - 2.5 = 0:
-1.5 k = 1 - 2.5
1 - 2.5 = -1.5:
-1.5 k = -1.5
Divide both sides of -1.5 k = -1.5 by -1.5:
(-1.5 k)/(-1.5) = (-1.5)/(-1.5)
(-1.5)/(-1.5) = 1:
k = (-1.5)/(-1.5)
(-1.5)/(-1.5) = 1:
Answer: k = 1